Recurrence Analysis in the Locomotion of Woodlice as a Function of Humidity Level - Ruiz, Jorge A.; Guerrero Sánchez, Cristina G. (Revista de Psicología, 2022)
The present study focuses on the use of quantitative recurrence analysis to analyse locomotor activity in woodlice as a function of the humidity level in the environment. Three subjects were exposed to four conditions in which the humidity level varied, from 32.9% to 94.9%. The movement of the animals in each humidity condition was videotaped. Using software for tracking insect trajectories (ID tracker) and algorithms programmed in R language, records, and representations of the displacement routes of woodlice were obtained as XY coordinates. The results showed differences in the level of activity, in terms of total distance travelled and in the variation of the displacement routes depending on the level of humidity, being the 50% humidity condition the one that controlled greater activity and greater regularity in the displacement patterns. Quantitative recurrence analyses, as well as corresponding recurrence plots, proved useful for the representation and analysis of activity in woodlice under different humidity level conditions.